Extensive sequence variation in rice blast resistance gene Pi54 makes it broad spectrum in nature - Thakur, Shallu; Singh, Pankaj K.; Das, Alok; Rathour, R.; Variar, M.; Prashanthi, S. K.; Singh, A. K.; Singh, U. D.; Chand, Duni; Singh, N. K.; Sharma, Tilak R. (Frontiers in Plant Science, 2015)
Rice blast resistant gene, Pi54 cloned from rice line, Tetep, is effective against diverse isolates of Magnaporthe oryzae. In this study, we prospected the allelic variants of the dominant blast resistance gene from a set of 92 rice lines to determine the nucleotide diversity, pattern of its molecular evolution, phylogenetic relationships and evolutionary dynamics, and to develop allele specific markers. High quality sequences were generated for homologs of Pi54 gene. Using comparative sequence analysis, InDels of variable sizes in all the alleles were observed. Profiling of the selected sites of SNP (Single Nucleotide Polymorphism) and amino acids (N sites ≥ 10) exhibited constant frequency distribution of mutational and substitutional sites between the resistance and susceptible rice lines, respectively. A total of 50 new haplotypes based on the nucleotide polymorphism was also identified. A unique haplotype (H_3) was found to be linked to all the resistant alleles isolated from indica rice lines. Unique leucine zipper and tyrosine sulfation sites were identified in the predicted Pi54 proteins. Selection signals were observed in entire coding sequence of resistance alleles, as compared to LRR domains for susceptible alleles. This is a maiden report of extensive variability of Pi54 alleles in different landraces and cultivated varieties, possibly, attributing broad-spectrum resistance to Magnaporthe oryzae. The sequence variation in two consensus region: 163 bp and 144 bp were used for the development of allele specific DNA markers. Validated markers can be used for the selection and identification of better allele(s) and their introgression in commercial rice cultivars employing marker assisted selection.